Mother and Child Health (MCH) Book Increasing Mother's Knowledge About Breast Milk Complementary Food (MP-ASI) - Arum Lusiana; Drayke Rosyana; Wiji Lestari; Rubiyana Islam Kartini (Midwifery and Nursing Research, 2022)
Background: In accordance with the Technical Guidelines for the Use of the MCH Handbook (Kemenkes, 2016), mothers of children under five are expected to understand and use the MCH handbook as a guide in caring for maternal and child health, and always strive to obtain health services according to standards as stated in the MCH handbook. Mothers of toddlers can use the MCH handbook for daily care of toddlers, including by utilizing information on how to feed according to the age of toddlers, how to care for children when they are sick, how to stimulate growth and development of toddlers, also being able to monitor the nutritional status of toddlers at any time after getting measurements. nutritional status both in posyandu and other health facilities. Methods: The research is Quasy Experimental Design with One Group Pretest Posttest Design and purposive sampling technique as many as 35 respondents. The research instrument used a questionnaire sheet. Data analysis using Wilcoxon test. Results: There was a significant difference between before and after health Education with KIA Book of mothers knowledge about complementary foods with a p-value of 0.000 less than 0.05 Conclusion: Health education with KIA Book about complementary food can be carried out routinely so that mothers understand better and can be practiced at home.